Konseling Kelompok Menggunakan Teknik Behavioral Contract Sebagai Layanan pada Peserta Didik yang Memiliki Perilaku Membolos - Busmayaril, Busmayaril; Havilla, Arfa (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
Truant habits will have a negative impact. Behavioral contracts are one technique to reduce the number of people targeted. So that this technique can update participants. This research is quantitative in the form of a quasi exprimental design with the design used in this study, namely: the design of a non-equevalent control group. There were two research groups namely: the experimental group and the control group which were both pretest and posttest. the results of consultations that have been given, there appears to be a change in the truant class to be lower, thus can be verified contractual behavior techniques can reduce truancy behavior of class XI students at Muhammadiyah 2 High School Bandar Lampung.